UBE2T/CDC42/CD276 signaling axis mediates brain metastasis of triple-negative breast cancer via lysosomal autophagy - Lin Li; Rong Fu; Yan Chen; Jin Yao; Xiaobing Jiang; Tao Liang; Jun jun Li; Qian zhi Chen; Liang Liang Shi; Ming Xing Xie; Xin Wei Qiao; Qi Hong Cheng; et al. (Journal for ImmunoTherapy of Cancer)
Background Advanced triple-negative breast cancer (TNBC) is prone to brain metastasis (BrM). The precise molecular mechanism responsible for this phenomenon has not yet been completely established, so it is vital to comprehend the molecular mechanism behind it.Methods The protein chip analysis was conducted to identify any abnormal UBE2T protein expression in TNBC, especially BrM. Here, we used public databases and bioinformatics analysis as well as clinical samples from different cohorts to investigate the interrelationship between UBE2T/CDC42/CD276. This predicted relationship was then repeatedly validated using different in vivo and in vitro experimental methods. Additionally, multiple experimental approaches were implemented, encompassing western blotting, Co-IP, GST pull-down, flow cytometry, mass spectrometry, immunofluorescence, immunohistochemistry, and qRT-PCR to reveal the molecular mechanism of UBE2T-mediated immune escape and BrM.Results Our results indicate that expressed at elevated levels in breast cancer, UBE2T is negatively linked to patient prognosis, especially in BrM of TNBC. Data from clinical samples from our different cohorts and TCGA indicate a significant correlation between UBE2T and immunosuppression. Mechanistically, UBE2T directly interacts with CDC42, promoting its K48-linked polyubiquitination and proteasomal degradation, thereby inhibiting CDC42 from degrading CD276 via the autophagy-lysosomal pathway, indirectly upregulating CD276 and thereby impairing the CD8+ T cells function, ultimately mediating tumor immune escape and BrM. Finally, animal experimental results also showed that inhibition of UBE2T elevated the TNBC sensitivity to immune checkpoint CD276 blockade and inhibited BrM of TNBC.Conclusions In conclusion, our results indicate a new mechanism whereby UBE2T-mediated ubiquitination positively controls the UBE2T/CDC42/CD276 axis to upregulate tumor cell expression of CD276 and thereby impair CD8+ T cells function, ultimately leading to tumor cell immune escape and BrM.